Four conceptions about Educational Planning in Argentina’s Educational Reform of the 1990s - Terigi, Flavia (Education Policy Analysis Archives, 2007)
This article analyses four patterns of planning in the educational reform in Argentina since the approval of the Federal Law of Education: first, planning focused on change, without enough attention to measures that could be useful to consolidate the educational system; second, planning was anchored in a vision of change that may be described as applicable and progressive, as if the impact that change may have on institutions and agents could be predicted; third, planning focused on centralized policies in order to homogenize and organize the systems, despite the goal of bringing the educational system under the jurisdiction of a federal-government-type system; and fourth, a work division was established between the Nation and the provinces, between planning and execution, and between technical and political issues of the reforms.